2021
DOI: 10.4081/mrm.2021.793
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone therapy and rates of secondary pulmonary and bloodstream infections in critically ill COVID-19 patients

Abstract: Background: Coronavirus disease 2019 (COVID-19) has become a pandemic. Bacterial superinfections seem to be associated with higher mortality in COVID-19 patients in intensive care units (ICUs). However, details on the prevalence and species distribution of secondary infections are limited. Moreover, the increasing use of dexamethasone may pose an additional risk of superinfections.Methods: We performed a single-center retrospective study of the clinical and microbiological characteristics of 154 COVID-19 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…The care of COVID-19 patients is associated with a more frequent use of personal protective equipment and a disruption of routine infection control practices. In addition, many hospitalized COVID-19 patients receive corticosteroid therapy, which may increase the risk of developing super-infections [ 5 ]. The risk for severe COVID-19 infection increased for patients with comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…The care of COVID-19 patients is associated with a more frequent use of personal protective equipment and a disruption of routine infection control practices. In addition, many hospitalized COVID-19 patients receive corticosteroid therapy, which may increase the risk of developing super-infections [ 5 ]. The risk for severe COVID-19 infection increased for patients with comorbidities.…”
Section: Discussionmentioning
confidence: 99%
“…However, most studies on the epidemiology of BSI during the COVID-19 pandemic have been of short duration and report on the early period of the pandemic [7][8][9], highlighting a need for data that capture the impact of clinically relevant COVID-19 variants, including the Delta variant, and reflect the use of immunomodulatory agents, which could affect the risk of secondary infections [10].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, clinical results from a small cohort indicated that inhibition of C5a reduced COVID-19 hyper-inflammation and improved lung function (Mastellos et al, 2020). Noteworthy, the hypothesis that the blockage of C5aR1 signaling would be beneficial to COVID-19 may open another important question related to secondary infections that are extremely common in COVID-19 patients and are a critical threat in the current treatments targeting the immune response (Lee et al, 2003; Hoenigl et al, 2022; Grasselli et al, 2021; Kooistra et al, 2021; Rothe et al, 2021). Although, inhibition of C5 by neutralizing antibodies has been associated with increased risk of bacterial infection due to the inhibition of the formation of the membrane attack complex, the selective targeting of C5a/C5aR1 signaling may avoid harmful anaphylatoxins-induced effects (Crew et al, 2019; Langereis et al, 2020).…”
Section: Resultsmentioning
confidence: 99%